Source-sink system analysis and sedimentary model of Cretaceous Yageliemu Formation in Xinhe area, northern Tarim Basin - HAO Jianlong; YANG Yufang; LI Shuai; ZHANG Li; MENG Luying; BI Xiaolong; YANG Qinchao (Youqi dizhi yu caishoulu)
Subtle lithologic traps are essential fields for oil and gas exploration in deep clastic rocks of Tarim Basin. The geological distribution pattern of favorable reservoirs in clastic rocks is a key challenge restricting efficient exploration and development. At present， breakthroughs in oil and gas exploration have been made in the deep reservoirs of the Lower Cretaceous Yageliemu Formation in Xinhe area of the northern Tarim Basin. In view of the limitation of wells， the distribution pattern of reservoirs in Yageliemu Formation urgently needs to be further clarified. This study took the plaeo uplift in Xinhe area of the northern Tarim Basin and the northern fault slope zone as examples and used prediction methods such as core analysis， seismic reflection identification， paleogeomorphology restoration， channel characterization， and seismic inversion constraint. Based on the theory of the source-sink system， the distribution characteristics of the source area， sediment transport channel， and fan delta in Yageliemu Formation on the plane and profile were analyzed. The research results indicated that fan delta sediments are developed in Yageliemu Formation in Xinhe area of the northern Tarim Basin. The sediment source of the fan delta in Xinhe area comes from the plaeo uplift in Xinhe area， and the development of multi-tributary incised valleys provides effective transportation channels for the fan delta sediments. The upstream area of Well W1 region in the southwest is characterized by shallow， narrow， straight， and small watershed area valleys. The small-sized fan delta sediments are developed in the incised valleys and feature late development. Well W2 region in the northeast has a wide， deep， multi-tributary， and large watershed area valley system in the upstream， with large-sized fan delta sediments developed， featuring large-scale early development， late regressive development， and early and late fan superposition.